Restoring nationalism among Indonesian descendants through Indonesian folklore teaching-class in Southern Mindanao Philippines - Hannun, Syaharanie Mulya; Passau , Sheila Nur Salsabila; Mocodompis, Geovani (Universitas Ahmad Dahlan, 2023)
The inability of speaking Bahasa Indonesia within children of Indonesian descendants abroad is quite concerning considering the fact that they receive little to no exposure of general knowledge of Indonesia. The purpose of this paper is to demonstrate how Davao international community service in the Philippines restore the nationalism among children of Indonesian descendants, with several projects delivered by students. The activity of delivering folklore to children in General Santos, Southern Mindanao, is one of the projects. The students conducted the project using the teacher-centered approach because it is believed to be able to improve the efficiency of learning. This project is successful measuring from how enthusiastic the taught children during class as the children were also gaining Bahasa Indonesia vocabulary proven by the fact that students were able to answer the quizzes with Bahasa Indonesia and slowly recognizing several places as well as its folklore.